Arquitetura RF-Miner: uma solução para localização em ambientes internos - Gomes, Eduardo Luis (2017)
The use of passive UHF RFID tags for indoor location has been widely studied due to its low cost. However, there is still a great difficulty to reach good results, mainly due the radio frequency variation in environments that have materials with reflective surfaces, such as metal and glass. This research proposes a localization architecture for indoor environments using passive UHF RFID tags and data mining techniques. With the application of the architecture in real environment, it was possible to identify the exact position of objects with the precision of approximately five centimeters and in real time. The architecture has demonstrated an efficient alternative for the implantation of indoor localization systems, besides presenting a derivation technique of direct attributes that contributes effectively to the final results.